Five new C19-diterpenoid alkaloids from Aconitum carmichaeli. (September 2015) - Qin, Xiangdong; Yang, Shu; Zhao, Yan; Gao, Yuan; Ren, Fucai; Zhang, Dongying; Wang, Fei
Graphical abstract: Highlights: Five new C19 -diterpenoid alkaloids were isolated from the aerial part of Aconitum carmichaeli . Carmichaenine A (1 ) and E (5 ) are featured with an 8- O -benzoyl substitution. Carmichaenine C (3 ) and D (4 ) are featured with a 14- O -benzoyl substitution. Carmichaenine B (2 ) and E (5 ) are featured with a OH substitution at C-10. Abstract: Five new aconitine-type C19 -diterpenoid alkaloids, namely, carmichaenine A–E (1 –5 ), and six known diterpenoid alkaloids, namely, 14-benzoylneoline (6 ), neoline (7 ), 10-hydroxyneoline (8 ), neolinine (9 ), songoramine (10 ), and songorine (11 ), were isolated from the aerial parts of Aconitum carmichaeli . Their structures were determined by extensive spectroscopic methods, especially 2D NMR analyses. Compounds8 and9 were isolated for the first time from A. carmichaeli .